2017
DOI: 10.1016/j.quageo.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal chronology of the Amazon forest: A record of biodiversity preserved by ancient fires

Abstract: The Amazon region holds a wide variety of ethnic groups and microclimates, enabling different interactions between humans and environment. To better understand the evolution of this region, ancient remains need to be analysed by all possible means. In this context, the study of natural and/or anthropogenic fires through the analysis of carbonized remains can give information on past climate, species diversity, and human intervention in forests and landscapes. In the present work, we undertook an anthracologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Some preliminary charcoal dating results of three studied plots may confirm this variability in return times and spatial patterns: an eastern Amazonia plot had fire estimates of 1134 years before present (BP) (charcoal in 10-20 cm) and 1620 years BP (30-50 cm); a northern Amazonia plot, 989 years BP (32 cm); and a south edge plot, a range of 96 years BP (10-20 cm), 806 years BP (20-30 cm), and 1372 years BP (150-200 cm). Other recent AMS results from the same region show a larger return interval in fire records for some sites, *6000 years (from 6876 to 365 years BP: Goulart et al 2017). Previous studies of soil charcoal have also shown a spatially localized and heterogeneous signature of fire on Amazon forests (McMichael et al 2012(McMichael et al , 2017.…”
Section: Discussionmentioning
confidence: 83%
“…Some preliminary charcoal dating results of three studied plots may confirm this variability in return times and spatial patterns: an eastern Amazonia plot had fire estimates of 1134 years before present (BP) (charcoal in 10-20 cm) and 1620 years BP (30-50 cm); a northern Amazonia plot, 989 years BP (32 cm); and a south edge plot, a range of 96 years BP (10-20 cm), 806 years BP (20-30 cm), and 1372 years BP (150-200 cm). Other recent AMS results from the same region show a larger return interval in fire records for some sites, *6000 years (from 6876 to 365 years BP: Goulart et al 2017). Previous studies of soil charcoal have also shown a spatially localized and heterogeneous signature of fire on Amazon forests (McMichael et al 2012(McMichael et al , 2017.…”
Section: Discussionmentioning
confidence: 83%
“…However, reported a difference in the composition of charcoal with ageing and Kaal and Rumpel (2009) found that PyC is affected by degradation processes in the soil, particularly the less intensely charred biomass. On the other hand, Goulart et al (2017) have pointed out that the interpretation of the results of the radiocarbon dating of charcoal fragments should be done with caution, since the age determination is less accurate in charcoal generated from long-lived trees than in that from young plants.…”
Section: Charcoal Pyrolysismentioning
confidence: 99%
“…This can be also used as a palaeoenvironmental source of information (Conedera et al, 2009;Knicker, 2011), including for the reconstruction of past vegetation (Figueiral and Mosbrugger, 2000) as well as for radiocarbon dating (Bird and Ascough, 2012). In this last case, the age of wood should be considered in the interpretation of the results, since the growth layers in long-lived trees can add years to age determination (Goulart et al, 2017). The pattern of lipid distribution in soils has also been used to detect soils affected by fires in geological times, especially when fire does not produce large amounts of charcoal (Eckmeier and Wiesenberg, 2009), e.g., in the case of non-woody vegetation fires (Figueiral and Mosbrugger, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the Brazilian Amazon, fire effects on tropical forests were first studied in the 1980's due to concerns of land clearing from wildfires (Uhl et al, 1981(Uhl et al, , 1982. While evidence of past fire has been reported for some old-growth Amazonian forests from charcoal radiocarbon dating and estimates of soil pyrogenic carbon storage (Sanford et al, 1985;Goulart et al, 2017;Koele et al, 2017), it is unclear whether past fire led to the selection of fire-adapted traits among Amazon forest tree species (Massi et al, 2017). If plant communities were adapted to past fires in Amazon forests, current burning would impact these differently (Brando et al, 2012).…”
Section: Introductionmentioning
confidence: 99%